Aerodynamics Concept Study of Electric Vehicles - Drag Reduction and Range Increase - Aktas, Umut; Abdallah, Kristian (My University, 2017)
As the greenhouse effect is causing climate instability all over the world, this issue must be adressed. One of the main contributor to this is the transportation sector which have been using fossil fuels to fire up the engines. Car manufacturers are today taken this issue in consideration and are starting to implement a more sustainable approach when developing and building new vehicles. NEVS is one of the car companies that have taken a major step towards creating a sustainable future. The approach is to develop pure electric vehicles and fleet sharing services driven by renewable sources which would contribute to a significant reduction of greenhouse gases. With the air resistance exerted on a driven vehicle being the largest energy consuming attribut, this thesis is done in collaboration with NEVS to study different approaches to reduce the aerodynamic drag. The study is divided into two parts, a theoretical part where a benchmarking study and a literature review is done and a practical part where concepts based on the theoretical part are chosen to be analyzed with CFD simulations. The simulation environment represents a highway drive where the aerodynamic energy loss is the highest. The simulated concepts resulted in drag reductions of up to 4% for the best cases. These cases corresponds to active aerodynamic features and is used in order to delay the separation at the rear-end of a vehicle. To conclude the study, it is shown that the aerodynamic performance of today’s vehicles have not yet reached its fully potential. As different concepts are analyzed it is found that with the use of aerodynamic features the drag can significantly be reduced hence increasing the range of electrical vehicles.
Keywords: Transport; Hållbar utveckling; Strömningsmekanik och akustik; Transport; Sustainable Development; Fluid Mechanics and Acoustics